Techno-economic assessment of redundancy systems for a cogeneration plant - Majid, M.A.A. (EDP Sciences, 2014)
The use of distributed power generation has advantage as well as disadvantage. One of the disadvantages is that the plant requires a dependable redundancy system to provide back up of power during failure of its power generation equipment. This paper presents a study on techno-economic assessment of redundancy systems for a cogeneration plant. Three redundancy systems were investigated; using public utility, generator set and gas turbine as back up during failures. Results from the analysis indicate that using public utility provides technical as well as economic advantages in comparison to using generator set or turbine as back up. However, the economic advantage of the public utility depends on the frequency of failures the plant will experience as well on the maximum demand charge. From the break even analysis of the understudied plant, if the number of failures exceeds 3 failures per year for the case of maximum demand charge of RM56.80, it is more economical to install a generator set as redundancy. The study will be useful for the co-generator operators to evaluate the feasibility of redundancy systems. Â© 2014 Owned by the authors, published by EDP Sciences.